A power-saving control strategy for reducing the total pressure applied by the primary air fan of a coal-fired power plant. (1st August 2016) - Wang, Yuelan; Ma, Zengyi; Shen, Yueliang; Tang, Yijun; Ni, Mingjiang; Chi, Yong; Yan, Jianhua; Cen, Kefa
Highlights: Primary air fans in coal-fired power plant usually consume unnecessary high power. A power-saving control strategy including two models is proposed for the primary air fan. The performance of the power-saving control strategy is verified with real time data. Power consumption reduction is obtained by experiments under different loads. Abstract: The high power consumption of auxiliary equipment, particularly that of the primary air fan, in a coal-fired power plant provides ample scope for reducing power consumption. Therefore, a power-saving control strategy for the primary air fan is proposed that automatically calculates a primary air pressure offset value in real time, which, when combined with the existing primary air pressure setting, reduces the total pressure, and correspondingly decreases the power consumption of the primary air fan while maintaining the mill outlet temperature within the optimum range. The power-saving control strategy implements two models that are respectively applicable to normal conditions and mill outlet over-temperature conditions. Mechanistic modeling is implemented for the model applicable to normal conditions. The model evaluates the mill inlet hot air damper opening for determining the potential for reducing the power consumption, the mill inlet cold air damper opening is applied for adjust the mill outlet temperature, and the total pressure and corresponding power consumption are thereby reduced. The other model is controlled by a conventional proportional derivative controller, which employs the deviation of the mill outlet temperature as its input. The proposed power-saving control strategy is applied to a 1000 MW commercial power plant, and the power consumption of the primary fan is demonstrated to be reduced by as much as 465 kW for a 500 MW load, resulting in a power consumption reduction of 15%.